The (Re)genesis of Values - Miles, Andrew (American Sociological Review, 2015)
Dual-process models of culture and action posit that fast, automatic cognitive processes largely drive human action, with conscious processes playing a much smaller role than was previously supposed. These models have done much to advance our understanding of behavior, but they focus on generic processes rather than specific cultural content. As useful as this has been, it tells us little about which forms of culture matter for action. Drawing on a cross-disciplinary set of theory and evidence, I argue that values are tied to many forms of behavior, across both contexts and cultures, and they operate in ways consistent with dual-process models. I illustrate the plausibility of these claims using data from the second wave of the European Social Survey, as well as real-time decision data from a large, online survey. I show that values predict self-reported behaviors in a variety of substantive domains and across 25 nations, and they operate using automatic cognitive processes. These findings suggest that values merit renewed theoretical and empirical attention.